PENGARUH FINANCIAL KNOWLEDGE DAN INTERNAL LOCUS OF CONTROL TERHADAP PERSONAL FINANCIAL MANAGEMENT BEHAVIOR - Sitorus, Mhd Raja Utama; Adlina, Hafiza (Peneliti.net, 2024)
The growth of young entrepreneurs in Indonesia has increased significantly with the demand to survive and develop for the continuity of entrepreneurship. The existence of small, micro, and medium enterprises is the largest part of the national economy and is community participation in various sectors of economic activity. This study analyzes how financial knowledge and internal locus of control affect personal financial management behavior. The form of research used is quantitative with an associative approach. The number of samples in this study was determined using the Lemeshow formula, with 96 respondents as samples. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression analyses, and hypothesis testing. The research results show that financial knowledge and internal locus of control significantly affect both partially and simultaneously personal financial management behavior in Jalan STM Medan City MSME players. The coefficient of determination test shows a close relationship between variables with an R-value of 0.700. The adjusted R square value also shows that the financial knowledge and internal locus of control variables contribute 48% to the personal financial management behavior variable. In comparison, other variables outside this research model influence the remaining 52%.